Analisis Pelaksanaan Pembelajaran Daring Masa Pandemi Covid-19 Siswa Kelas V Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis - Mardin Mardin; Moch. Hasyim Fanirin; Dadan Mardani (Pusat Riset dan Inovasi Nasional, 2023)
In the midst of the current pandemic situation, the process of learning activities must still be carried out even though not directly face to face. This, of course, requires the right media in online learning to support the application of online learning at Madrasah Ibtidaiyah MI Muhammadiyah Sukajati Haurgeulis. This study aims 1) To find out the implementation of online learning during the Covid-19 Pandemic for Class V Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis. 2) To find out the obstacles to implementing online learning during the Covid-19 Pandemic for fifth grade students at Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis This research method uses a qualitative descriptive approach using a qualitative naturalistic approach. the object of this research is the Head of Madrasah teachers of class V and students of class V Madrasah Ibtidaiyah Islamic Community Association Madrasah Ibtidaiyah Muhammadiyah Sukajati Haurgeulis . The data source of this research uses primary data and secondary data. Data collection procedures using observation, interviews and documentation. The results of the study show that the implementation of online learning is very helpful in the process of conveying information from the material to be studied. In online learning media besides that the WhatsApp application is a means of learning activities, so that the learning process becomes more effective and makes it easy for teachers and students in the communication process while carrying out online learning. Obstacles in using the WhatsApp application in online learning, namely signal interference which results in WhatsApp being difficult to access, another obstacle, namely the lack of effectiveness in the learning process, teachers cannot directly see the earnestness of students, cellphone memory which quickly fills up with documents that are difficult to enter will be hampered